The Meeting of the Two Inhabitants and Ways to Dispose of It in the Holy Quran | التقاء الساكنين وسبل التخلص منه في القرآن الكريم - Abdel Kader Sellami; Asma Abidat (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2019)
The next intervention seeks to market its models in the Arabic language and to stand on another of the Holy Quran in order to get rid of it as a fraction, overgrowth, and open and darkerThe meeting of the inhabitants of the Holy Quran is a subject worthy of study and research as a phenomenon of linguistic phenomena that make a difference in the construction of words in the Arabic language and pronunciation and expression; it is a phenomenon worthy of standing and study for repeating in our speech.In this paper the researcher will try to a short Schaech map of these in the language of Arab’s and in the Holy Quran.